2016
DOI: 10.4103/2211-4122.183748
|View full text |Cite
|
Sign up to set email alerts
|

The association of left ventricular mass index with metabolic syndrome in comparison to hypertensive patients

Abstract: Background and Objectives:The metabolic syndrome (MS) is a condition associated with the clustering of risk factors including high blood pressure (BP), abdominal obesity, glucose intolerance, and dyslipidemia; which increases cardiovascular morbidity and mortality. High burden of subclinical disease component of MS contributes to the increased risk by causing left ventricular (LV) hypertrophy, thereby affecting long-term prognosis. This cross-sectional study uncovers the role of LV hypertrophy (LVH) and LV mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In a case–control study, North Indian patients with metabolic syndrome were reported to have a higher exposure rate of LV hypertrophy (44 % vs 32 %; relative risk: 1.38; odds ratio: 1.67 [95 % CI 0.53, 5.29]) compared to hypertensive patients without T2DM. 45 De Simone also showed that the hazard of HF is increased by 1 % for each 1 % increase in excessive LV mass (HR: 1.01; 95 % CI 1.02, 1.04; p = 0.0001) after adjusting for age, sex, obesity, diabetes, arterial hypertension, and antihypertensive treatment and accounting for incident myocardial infarction. 43 However, none of the Indian studies including ours have evaluated the risk of adverse CV events associated with LV GLS values and LV mass as per our knowledge.…”
Section: Discussionmentioning
confidence: 94%
“…In a case–control study, North Indian patients with metabolic syndrome were reported to have a higher exposure rate of LV hypertrophy (44 % vs 32 %; relative risk: 1.38; odds ratio: 1.67 [95 % CI 0.53, 5.29]) compared to hypertensive patients without T2DM. 45 De Simone also showed that the hazard of HF is increased by 1 % for each 1 % increase in excessive LV mass (HR: 1.01; 95 % CI 1.02, 1.04; p = 0.0001) after adjusting for age, sex, obesity, diabetes, arterial hypertension, and antihypertensive treatment and accounting for incident myocardial infarction. 43 However, none of the Indian studies including ours have evaluated the risk of adverse CV events associated with LV GLS values and LV mass as per our knowledge.…”
Section: Discussionmentioning
confidence: 94%
“…The association between anthropometric measures, in particular BMI and abdominal circumference, with metabolic syndrome is well established [28]. Similarly, several anthropometric variables, including BMI, waist circumference, waist-hip ratio, and waist-length ratios are associated with LVM in adults [29][30][31][32][33][34]. The pediatric literature relating et al raise the question whether further increases in BMI are associated with an increased severity of left ventricular hypertrophy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome, central obesity, and diabetes substantially increase risk for VH/HF, independent of their common association with hypertension [ 447 , 448 , 449 , 450 , 451 , 452 , 453 , 454 , 455 , 456 , 457 ]. These disorders are characterized by high tissue exposure to free fatty acids, and there is reason to suspect that increased exposure to long-chain saturated fatty acids is a mediator of this increased risk.…”
Section: Protective Diet and Lifestyle Measuresmentioning
confidence: 99%